Učbeniki v postsocialističnih državah: nastavki za primerjalno analizo - Kovač, Miha (Knjižnica, 2004)
In its first part, the paper analyses the ambiguous nature of the book as a medium: its physical production and its distribution to the end user takes place on a market basis: on the other hand, its content is predominantly consumed in a sector that was at least in the continental Europe traditionally considered as public and non-profit making. This ambiguous nature of the book and with it the impact of the market on the organization of knowledge in book format remains a dark spot in contemporary book research. Onthe other hand, textbooks are considered as ephemera both in contemporary education and book studies. Therefore, research on textbooks publishing modelscould be considered as a blind-spot of contemporary social studies. As aconsequence, in the majority of European countries, textbook publishing and the organization of the textbook market are considered as self-evident. Throughout a comparative analysis of textbook publishing models in small transitional and developed countries, the paper points out that this self-evident organization of the textbook market is always culturally determined. In its final part, the paper compares different models of textbookpublishing and outlines the scenarios for the development of the Slovene textbook market.
Keywords: učbeniki; založništvo; knjižni trg; knjigotrštvo; vzgoja in izobraževanje; primerjalne analize; learning; učenje; tranzicija